Negotiation of Strategic Distance: A Smart City Project with Japanese Official Development Assistance in Bang Sue, Thailand - Kie Sanada; Kentaro Kuwatsuka (International Quarterly for Asian Studies, 2024)
The existing critical literature constructs Smart Cities (SC) as sites of technocratic governance, hidden within a socio-technically imagined utopian discourse that originated in the “Global North” but has already deeply penetrated the “Global South”. The substantial inflow of SC-related foreign investment into emerging Asian countries, such as Thailand, has motivated this paper to shed new light on the extensive nature of investment in the region. The authors have chosen to examine a SC project supported by Japanese Official Development Assistance in Bangkok’s Bang Sue district. This case study enables them to investigate the SC concept within the broader context of international politico-economic power struggles, particularly between Thailand and Japan in the realm of international cooperation. Using the concept of strategy, this study conceptualises the establishment of Smart Cities as each nation’s approach to advancing both national economic interests and international security. The examination of the policy history of SC conception in Thailand and Japan reveals diverse motivations behind these initiatives. Thailand seeks to shift its economic weight to the digital and knowledge sectors, while Japan targets economic and security enhancements in the Indo-Pacific region. Despite the common strategy of developing SC infrastructure in the Bang Sue area, the analysis identified nuanced differences in their goals. Further scrutiny of project documents revealed: 1) strategic distancing within the project, 2) technocratic traits within the project process, and 3) the role of socio-technical utopian discourse beyond ideology.